Effects of Second-Hand Smoke on Pancreatitis in Children. Issue 5 (May 2019) - Ballengee, Cortney R.; Brooks, Peter; Leong, Traci; Geem, Duke; Freeman, A. Jay
Abstract : Objectives: Pediatric pancreatitis incidence is increasing, but little is known about risk factors. Smoking increases the risk for adult pancreatitis and has been shown to affect CFTR function in vitro. Therefore, we evaluated passive smoke exposure effects on disease outcomes in children with various pancreatitis etiologies. Methods: We conducted a 5-year retrospective chart review of patients admitted for pancreatitis to Children's Healthcare of Atlanta. Demographic data, etiology of pancreatitis, and number of hospitalizations with length of stay (LOS) were compared with smoking exposure, obtained through telephone query. Results: Of the 134 subjects admitted for pancreatitis, 90 reported no smoke exposure (none), 33 reported outdoor smoke exposure (outside), and 11 reported exposure to indoor smoking (inside). Average hospital admissions ( P = 0.038) and LOS ( P = 0.004) were significantly higher among subjects with inside smoke exposure compared with those with outdoor or no exposure. Average hospital admissions were significantly higher in subjects with CFTR mutations compared with those with nongenetic or other genetic etiologies ( P ⩽ 0.001). Conclusions: Second-hand smoke exposure may increase hospital admission rates and LOS for pediatric pancreatitis. Children with an identifiable CFTR mutation may have increased risk for hospital admissions compared with those who do not. Abstract : Supplemental digital content is available in the text.